Ensino de Libras para ouvintes: design educacional de ambiente de aprendizagem dialógico (AVA) - Torres, Regina Célia (2022)
With the recognition of the Brazilian Sign Language - Libras through the publication of Law n° 10,436 of 2002 and Federal Decree n° 5,626 of 2005, which regulated it, the teaching of the language became mandatory in several higher education courses. In addition, the actions of the “Living Without Limits Plan”, through Decree n° 7,612 of 2011, created conditions for expanding the training of professionals in the field of deaf education at different levels of sign language. However, despite this, there is a lack of teaching materials aimed at teaching sign language as a second language (L2), especially at more advanced levels. Based on the construction of an interdisciplinary dialogue between Education, Design and Technology, this thesis aimed to develop educational material to support the study of Libras as a second language (L2) for students enrolled in a higher education course in translation and interpretation in Libras/Portuguese Language, conceived under the dialogical perspective of the language in effective use as a differential. Through the application of methods and techniques of Design, we sought to identify how this area of knowledge may help in the configuration of pedagogical materials, and enhance the learning of knowledge of a language in the visual-spatial modality. Through qualitative research, in the research-application model in education, the instruments and procedures for data collection were explored using a questionnaire and focus group technique. In this sense, we have the following assertion as a thesis: That from a visual language guided by the principles raised by learners and educators, technology is placed as a pedagogical device to support education, teaching Libras as L2. This study was built based on the cultural historical theory proposed by Vygotsky, and presents issues related to language teaching, new technologies, visual culture, imagery resources and visual pedagogical practices. As a final product, a dialogic learning environment (VLE), structured in order to meet the demands identified with the end users, being presented concepts in Libras, dialogues in Libras, activities of Libras for Libras, activities of Libras for the Portuguese Language and theoretical aspects of the language. This thesis aims to contribute to the planning of educational materials that consider the specificity of the Brazilian Sign Language and, consequently, create more effective and interactive teaching and learning processes; in addition to innovating by reconciling the visual aesthetics and the discursive domain present in the activities proposed in the dialogic learning environment (VLE) developed.